Dampak Mikroplastik terhadap Ekosistem Pesisir: Sebuah Telaah Pustaka - Kastilon, Kastilon; Novianto Saputra, Dhendi; Ritonga, Abdullah Ibrahim; Reflis, Reflis; Satria P. Utama (Yayasan Literasi Sains Indonesia, 2024)
Microplastics can cause physical, chemical, and biological damage to marine organisms. Small microplastic particles can become trapped in the tissues of organisms or be ingested by marine biota, causing physical injuries and even death. The findings of this study are expected to provide information to companies, governments, and the public regarding the impact of microplastics on coastal ecosystems, as well as recommendations for solutions that can be implemented to minimize the pollution impact. The study results indicate that microplastics can also absorb hazardous chemicals and pollutants, which can enter the bodies of marine organisms and cause toxicity. The accumulation of microplastics in the bodies of organisms can impact higher-level organisms in the food chain, including humans. In this regard, recommendations for strategies and public awareness are necessary to safeguard the environment and ensure a healthy life. The public should play an active role in controlling environmental impacts, reducing the use of single-use plastics, and implementing proper waste management systems. Additionally, governments need to create effective national policies for managing plastic waste, implementing the 4R hierarchy, and educating the public to increase awareness of the negative impacts of microplastics on coastal ecosystems. Lastly, continuous research and monitoring of microplastics in coastal ecosystems are necessary to develop more effective control strategies.